Derivatives of 4-methyl-1,2,3-benzoxathiazine 2,2-dioxide as selective inhibitors of human carbonic anhydrases IX and XII over the cytosolic isoforms I and II - Jekaterīna Ivanova; Morteza Abdoli; Alessio Nocentini; Raivis Žalubovskis; Claudiu T. Supuran (Taylor & Francis Group, 2023)
A series of 4-methyl-1,2,3-benzoxathiazine-2,2-dioxides with various substituents in 5, 6 or 7 positions was obtained from corresponding 2'-hydroxyacetophenones in their reaction with sulphamoyl chloride. 6- and 7-aryl substituted 4-methyl-1,2,3-benzoxathiazine-2,2-dioxides were obtained from aryl substituted 2'-hydroxyacetophenonesprepared from 4- or 5-bromo-2'-hydroxyacetophenones via two-step protocol. 4-Methyl-1,2,3-benzoxathiazine-2,2-dioxides were investigated as inhibitors of four human (h) carbonic anhydrase (hCA, EC 4.2.1.1) isoforms, off-target cytosolic hCA I and II, and target transmembrane, tumour-associated hCA IX and XII. Twenty derivatives of 4-methyl-1,2,3-benzoxathiazine 2,2-dioxide were obtained. With one exception (compound2a), they mostly act as nanomolar inhibitors of target hCA IX and XII. Basically, all screened compounds express none or low inhibitory properties towards off-target hCA I. hCA II is inhibited in micromolar range. Overwhelming majority of 4-methyl-1,2,3-benzoxathiazine 2,2-dioxides express excellent selectivity towards CA IX/XII over hCA I as well as very good selectivity towards CA IX/XII over hCA II.